Research on the Application of AIGC in the Film Industry - Mingda, Gao; Wai Yie, Leong (INTI International University, 2024)
This paper explores the feasibility of applying artificial intelligence generated content (AIGC) technology in the film industry, analyzes its potential to replace certain positions in the film industry, and explores how to integrate AIGC into different aspects of film production such as script writing, video production, and audio processing through experimental creation. Comparative research and experimental methods are used to explore the feasibility of applying AIGC in the film industry at this stage. The more mature AIGC platforms such as ChatGPT 4.0, Stability AI, Midjourney, and Suno V3.5 are used for research to optimize the film production process and provide some reference for other researchers. The findings suggest that AIGC could redefine industry standards and democratize the filmmaking process, enabling more creators to access sophisticated tools and produce high-quality content. This paper ultimately provides a roadmap for the strategic adoption of AIGC in filmmaking, outlining best practices and future research directions for a sustainable and creative AI-powered film industry.